Manga matrix's approach to creating Indonesian ghost game visual characters on Dreadeye VR - Ricky Widyananda Putra (International Journal of Visual and Performing Arts, 2022)
Visual imagery is the most important part of game design. Game designers should pay particular attention so that the visual character of the game can be effectively realized and able to convey the depth of its visual meanings. Taking use of the widespread fear of the Indonesian Ghost's appearance, the game is able to present challenges to its players. This study aims to develop the creation of character designs, especially by elevating visual images of Indonesian ghosts into visual characters' in-game media. The method for designing Indonesian ghost characters is to dismantle the visual image of Indonesian ghost characters in the Dreadeye VR game. The strategy is to consider the following three components: (1) the matrix of shapes, (2) the costume matrix, and (3) the matrix of traits. All three were analyzed with the approach of manga matrix theory. This research has led to the emergence of relatively distinct ghost figures that are frequently feared by Indonesians, such as pocong, kuntilanak, and tuyul. By examining the matrices of the shape, costume, and nature of each character of the three Indonesian ghosts, it is possible to conclude that to create visual characters of Indonesian ghosts, game designers must identify these three components, while the contribution of this research is to provide a visual image analysis model including shape imagery, costume imagery, and traits imagery of Indonesian ghosts used in the Dreadeye VR Game in Indonesia.